Edukasi Haidh Dalam Perspektif Ilmu Agama dan Medis Remaja Masjid - M. Munif Rohmatulloh; Mustajib (LP3M IAIFA Kediri, 2020)
The current social environment of society that does not support religious cultivation for adolescents must be made aware and resolved by the community itself. Based on this context, this community education program is implemented and directed to provide religious strengthening for adolescents through education. This community education activity is seen as quite successful in resuscitating the community about the current environmental conditions. In education also emerged good cooperation and communication between researchers and the community and the role of the people of Bangkok Village actively in the successful program. The number of educational participants who participated showed the success of learning in order to strengthen religion for adolescents. The success of this program can also be used as a model of implementing religious reinforcement elsewhere by adjusting the existing context.